(untitled) (Italian Journal of Public Health, 2012)
Background: drug abuse is a social and public health problem, with high costs to society. It is, therefore, important to develop effective treatments for this problem, and evaluate these by identifying determinants of successful outcomes in order to plan more efficient public health interventions.The methadone maintenance treatment (MMT), at an appropriate dosage, is recognized as the most effective therapy for opiate addiction, but it is very important to consider the motivation and stage of change of patients for reaching treatment success. These must also be considered when investigating the determinants of MMT success. The aim of this study is to identify the determinants of successful MMT given to “heroin-addicts" attending the drug addiction Services of the Local Health unit of the Italian autonomous Province of Trento in two groups of patients, as outlined below. Methods: a retrospective cohort study was conducted. 393 heroin addicted patients, admitted for the first time to a MMT program in the drug addiction Services of Trento Local Health unit between the years 2000-2008, were considered. Patients were divided into 2 groups on the basis of the objective of treatment suggested by the clinical team and negotiated with the patient: group a labelled high evolution, group B low evolution.High evolution corresponds to a clinical situation in which, by opinion of the operators, the patient has the ability to pursue goals of change. In these cases, the methadone treatment is aimed at reaching a drug free condition and the goal/outcome is opioid abstinence (negative urine results in 90%-100%). Low evolution is characterized by little or no compliance to the assessment and/or therapeutic proposal aimed at achieving change. In these cases, the methadone treatment is aimed at achieving two or more of the following objectives: retention in treatment regimens, improvement of health and/or psychological distress, reduction of criminal activity, of overdose risk, of risk behavior and increase of work.The probability of successful treatment was estimated by means of a multivariate logistic model. The odds ratios and 95% confidence intervals were calculated. Results: for group a, the absence of previous admissions into rehabilitation centres, and social therapy associated with MMT were associated to an overall successful treatment.For the group B, the determinants of successful MMT were: having started treatment after 35 years, having a low educational level, not having previous imprisonments and not assuming the substance more than once a week. Conclusions: the “program" related factors usually considered (like for instance: previous admissions into rehabilitation centres, social therapy) and “individual" ones (like for instance: having started treatment after 35 years, having a low educational level, not having previous imprisonments and not assuming the substance more than once a week ), influenced the effectiveness of MMT in a different way: if for patients in high evolution group the determinants of success were more associated to “program-related" factors, in the case of the low evolution group, the positive outcome seemed to be mostly related to “individual" factors....